Sex Differences in Psychological Adjustment to Unemployment and Reemployment: A Question of Commitment, Alternatives or Finance?. (4th August 2014) - Shamir, Boas
Abstract : Previous research has found a weaker relationship between employment status and psychological well-being among women than among men. I examine three alternative explanations for sex differences in reactions to unemployment: (1) Women have a lower commitment to the work role. (2) Women are more likely to perform family roles which substitute for employment. (3) Women are less affected financially by unemployment. I use survey data on unemployed and reemployed men and women in Israel to assess hypotheses derived from these explanations. The results confirm that employment status has stronger effects on depressive affect, anxiety, and morale for men than for women. At least in this highly educated sample, the differing financial implications of unemployment for married men and women best explain sex differences in psychological well-being.